Educação de pessoas idosas: um estudo de caso da Universidade da Maturidade no Tocantins - Pereira, Fabíola Andrade (2016)
The present study intends to investigate lifelong learning related to the third age. The locus of the study is youth and adult education (YAE) as a theoretical and practical field, in which we seek to understand to what extent the phenomenon of ageing has been considered a substantive part of discussions and actions which involve the field. We start from the premise that the different experiences of group learning mentioned above have assumed an important role in the face of the phenomenon of ageing and that this, in its turn, constitutes an inherent part of the discussions which involve lifelong learning since it seeks to offer education without age limits. This concern also has as its background the recognition that the number of elderly people is growing as is life expectancy worldwide, a fact which has raised, amongst other questions, the expansion of studies directed to the theme and the delivery of actions and educational practices destined to this public in the most diverse times and spaces, just like the very universities which have sought to consolidate their mission as an environment which integrates teaching, research and extension through projects and programmes. In that sense, the point of departure for this study was the experience with the elderly from the University of Maturity in Tocantins (UMA). We set out to discuss a subject who is ignored on different fronts (by welfare, sanitary and educational policies). A subject who is unable to find space in the public and state sphere to renew and update his knowledge, and who has encountered in the experience of the university a means of reinventing and reaching a new understanding of him/herself as an incomplete being and, therefore, conscious of his/her incompletion. Methodologically this study is based on bibliographic and, at times, explicative research. Taking the University of Maturity at the Federal University of Tocantins as its reference, the methodology has recourse to the case study and makes use of ethnography as a method of analysis.